(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This essay aims to analize decision no. 84 of 2016 of the Italian Constitutional Court, on the matter of scientific research on embryos. In particular the essay dwells with the problematic acknowledgement of the embryo dignity. The Author considers this aspect in the context of the relation between scientific evolution and legislative discretionality, taking into account the other decisions of the Court on the matter of medically assisted procreation.